Legitime Portie In the Perspective of Civil Law on the Division of Inheritance - Mariana Mariana; Benny Djaja (PT Publikasiku Academic Solution, 2023)
This research examines who is prioritized and whether they are prioritized by lawful heirs or heirs according to a will. The research method used is descriptive analysis, a normative-juridical approach, namely library research conducted on secondary data. The results of the study concluded in the Civil Code that the arrangement of heirs with a will must be prioritized with exceptions as long as the contents and distribution in the will do not conflict with the law. The legal considerations are that the will is the final will of the heir but still does not violate the absolute portion of the legitimacy of the heirs. If the will of the heir violates the absolute portion of the legitimacy of the heirs, they may request cancellation, correction, or reduction of the testament.